2019
DOI: 10.3389/fnins.2019.00604
|View full text |Cite
|
Sign up to set email alerts
|

Canine Cognitive Dysfunction and Alzheimer’s Disease – Two Facets of the Same Disease?

Abstract: Neurodegenerative diseases present a major and increasing burden in the societies worldwide. With aging populations, the prevalence of neurodegenerative diseases is increasing, yet there are no effective cures and very few treatment options are available. Alzheimer's disease is one of the most prevalent neurodegenerative conditions and although the pathology is well studied, the pathogenesis of this debilitating illness is still poorly understood. This is, among other reasons, also due to the lack of good anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 201 publications
(281 reference statements)
2
49
0
Order By: Relevance
“…Some literature exists on the impact of gonadectomy on cognitive function in dogs, most notably regarding Canine Cognitive Dysfunction (CCD), which is a behavioral syndrome affecting older dogs that shares many pathophysiological and behavioral hallmarks with human Alzheimer's Disease (AD), including progressive cognitive impairment, loss of normal sleep patterns, increased anxiety, and aimless wandering as well as Amyloid-beta and possibly tau pathology in the brain [230][231][232]. In this context, female and gonadectomized dogs have been shown to be significantly more likely to show signs of CCD than intact and male dogs in a study of n = 325 geriatric dogs aged nine or older [233].…”
Section: Cognitive Functionmentioning
confidence: 99%
“…Some literature exists on the impact of gonadectomy on cognitive function in dogs, most notably regarding Canine Cognitive Dysfunction (CCD), which is a behavioral syndrome affecting older dogs that shares many pathophysiological and behavioral hallmarks with human Alzheimer's Disease (AD), including progressive cognitive impairment, loss of normal sleep patterns, increased anxiety, and aimless wandering as well as Amyloid-beta and possibly tau pathology in the brain [230][231][232]. In this context, female and gonadectomized dogs have been shown to be significantly more likely to show signs of CCD than intact and male dogs in a study of n = 325 geriatric dogs aged nine or older [233].…”
Section: Cognitive Functionmentioning
confidence: 99%
“…As noted above, we and others have found that oral infection of mice with P. gingivalis results in translocation to the brain, resulting in neurodegeneration and AD pathology, while other oral bacteria did not translocate . Because dogs are naturally infected with the closely related species, P. gulae, and commonly develop both periodontal disease and canine cognitive dysfunction associated with cerebral neuropathology, including amyloidosis, tau hyperphosphorylation and neuronal loss that resembles AD in humans, we aimed to examine the presence of P. gulae and associated gingipain proteases in dogs and investigate the pharmacology of the selective Kgp inhibitor COR388 in these animals. The prevalence of periodontal disease in dogs increases with age, with 40.8% of dogs 1‐4 years old, and 53.6% of dogs 5‐8 years old, having evidence of the disease, with prevalence increasing to >85% in dogs older than 8 years of age .…”
Section: Introductionmentioning
confidence: 99%
“…As dogs and humans share their environment and have similar lifestyles, they also suffer from some similar diseases. For instance, canine cognitive dysfunction is in many aspects similar to human Alzheimer’s disease [ 29 ] and represent an interesting model to study this debilitating disease. Canine cognitive dysfunction is interesting disease for cell replacement therapy by transplanting neurally differentiated ASCs into the canine brain.…”
Section: Discussionmentioning
confidence: 99%